Impact of prenatal risk factors in attention deficit hyperactivity disorders: potential for gene-environment interactions - Rodriguez,A (Psychiatry, 2008)
Attention deficit hyperactivity disorder (ADHD) is a multifactorial disorder and both genetic and environmental factors have been implicated in its etiology. Yet, the interaction between genes and environment is seldom studied directly. This article considers the plausibility of nicotine exposure during prenatal development as well as postnatal factors in the etiology of ADHD. The few existent studies show inconsistent results, but provide preliminary evidence suggesting that nicotine exposure together with genes in the dopaminergic system confer risk for ADHD. Factors affecting resilience during prenatal and postnatal development remain virtually unexplored. Recommendations for future research are provided. © 2008 Elsevier Ltd. All rights reserved.